Republic of Lithuania : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper and Statistical Appendix analyzes four issues relevant to the achievement of high-quality economic growth in Lithuania, namely the composition of government expenditure, financial sector development, foreign direct investment, and entry and exit of commercial enterprises. The paper reviews the composition of public expenditure and draws some comparison with other countries in the region. A discussion of the reforms to date in the area of public expenditure management is presented. The paper also highlights the possible pressures for additional expenditure in a number of areas.